The Urgency of Gender Equality for Women Workers in Indonesia: Urgensi Kesetaraan Gender Bagi Tenaga Kerja Wanita Di Indonesia - Al Asrori, M Hasan; Zihni Zulfahmi, Amirul Zidan (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2023)
The legal protection of women workers is an essential part of the concept of human rights and gender equality. The aim of this study is to study the legal protection of female workers from the perspective of human rights and gender equality. The study identifies methods of normative jurisprudence, i.e. by examining literature or articles – articles and legislative regulations – of applicable law and related to the problem studied. Studies of literature have found that the protection of female workers is part of human rights and women are at a vulnerable level. Legislative regulations – laws and international conventions have been established to protect and guarantee women's rights and gender equality, however, some parties have blocked Indonesia from moving towards gender. This is due to the patriarchal culture of more respect for women at home and men at work, the lack of awareness of women's rights, and the stigma of the society that believes that women are low human beings and strong men. Gender protection and equality must be fought in the light of the numerous cases of discrimination, violations of women's rights and duties, and gender inequality in Indonesia.